Immune suppression in MTAP-deficient cancers via glutamate metabolism and CXCL10 downregulation - Chang, Wen-Hsin; Zhang, Jun; Hong, Qi-Sheng; Chen, Ching-Hsien (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have transformed cancer therapy; however, their efficacy remains limited in certain tumor subtypes, including those deficient in methylthioadenosine phosphorylase (MTAP). MTAP-deficient cancers are characterized by immunosuppressive tumor microenvironments (TMEs) and poor T cell infiltration, as suggested by large-scale transcriptomic analyses. Yet, the underlying mechanisms and therapeutic vulnerabilities remain poorly defined.MethodsWe employed murine tumor models and transcriptomic profiling to investigate the immunosuppressive features of MTAP-deficient tumors. To identify actionable vulnerabilities, we conducted a high-throughput screen using the LOPAC1280 compound library. Functional assays were performed to evaluate the effects of candidate compounds on tumor growth and immune signaling.ResultsMTAP-deficient tumors exhibited significantly reduced CD45+ immune cell infiltration and resistance to ICI therapy. Transcriptomic analyses revealed that MTAP-deficient cancer cells reprogram immune signaling pathways and suppress the expression of CXCL10, a key chemokine for T cell recruitment, thereby contributing to a non-inflamed, “cold” TME. High-throughput screening revealed an increased dependence on glutamate metabolism in MTAP-deficient cells. Several glutamate pathway inhibitors, including the clinically tested glutaminase inhibitor CB-839, selectively impaired their growth. Remarkably, CB-839 also restored CXCL10 expression, particularly under immune co-culture conditions, indicating a dual effect of direct cytotoxicity and immune activation.ConclusionThese findings uncover a novel link between glutamate metabolism and immune modulation in MTAP-deficient tumors. Our study provides mechanistic and preclinical support for targeting glutamate pathways to both suppress tumor growth and convert immune-cold tumors into more immunoresponsive states, offering a promising strategy to enhance ICI efficacy in this challenging cancer subtype.